Heterogeneity in the CD200R paired receptor family. - Akkaya, M; Barclay, N (2010)
Paired receptors are groups of closely related membrane proteins that have the potential to either inhibit or activate. The CD200R family consists of one inhibitory member, CD200R and various numbers of activating genes according to species with three defined in C57BL/6 mice. A genomic PCR strategy was used to examine the repertoire of genes in both laboratory and wild-derived mice. Most mouse strains tested (18/22) had three activating genes, and 16 of these had either the combination of CD200RLa, Lb, and Lc or CD200RLa, Lb, and Le. The Lc and Le genes were mutually exclusive and were equally common (10 strains). Wild-derived mice varied more with one example of strains with one, two, and four activating genes. An inhibitory CD200R gene was detected in each mouse strain, although two slightly different sequences were found in both laboratory and wild-derived mice. This diversity is probably being driven by pathogens but is less extensive than for many NK paired receptors such as KIR and Ly49. It is possible that myeloid paired receptors are involved in immune regulation of responses against pathogens rather than directly killing infected cells as for NK cells and, hence, under less intense evolutionary pressure.